Instructional Strategy: Improving Writing Descriptive Text through POWER Strategy - Suci Suryawati, Sri; Aryanika, Septa; Husna, Asmaul; Faridatul Hasanah, Ida (JET ADI BUANA, 2025)
This study explored the effectiveness of the POWER (Prepare, Organize, Write, Edit, Revise) strategy in improving seventh-grade students' ability to write descriptive texts at MTS Miftahul Ulum Bandar Lampung. Employing a classroom action research approach, the study followed four stages: planning, action, observation, and reflection. It was conducted over three cycles with 20 students from class VII-A during the 2024/2025 academic year. Data were collected using both quantitative and qualitative methods. Quantitative data were derived from written tests administered at each stage, while qualitative data were gathered through observation sheets. The results showed that the POWER (Prepare, Organize, Write, Edit, Rewrite) strategy effectively improved the descriptive writing ability of Grade VII-A students at MTs Miftahul Ulum, Bandar Lampung. The students' average score improved from 50.75 in the pre-test to 80.35 in the post-test in the third cycle, with 85% of the students achieving the KKM score. This strategy helps students to understand the writing process systematically and enhances their independence. Learning becomes more purposeful, interactive and enjoyable. The POWER strategy is recommended as an effective method for teaching descriptive writing.